Experimental optimization tool for the development of muffins with high technological and nutritional value using whole flours of rice, red sorghum and carioca bean (Research, Society and Development, 2022)
Gluten-associated enteropathies have been on the agenda today. With this, the food industry shows interest in adapting conventional foods made with wheat flour to gluten-free flour to meet this market niche. Thus, this work evaluated the physicochemical and proximate characteristics of the dough and muffin-type cake using wholemeal rice, red sorghum and carioca bean flours. The performance of the flours was investigated through a Simplex-Centroid Mixture Design of three independent variables: whole rice flour (x1), whole red sorghum flour (x2) and whole carioca bean flour (x3). The dependent variables evaluated were the physicochemical and technological properties of the batters and cakes. The results were assessed using the Response Surface Methodology as an experimental strategy (R2 > 0.80 and p-value < 0.10). Observing the parameters that were significant and evaluating the desirability of the parameters in the cake, an optimal point was set by a formulation composed of 91 % whole red sorghum flour and 9 % whole carioca bean flour, with 75 % of the mathematical models validated directly, and a desirability degree of 0.8784. The optimized muffin had a high content of dietary fibers, proteins and ashes, suggesting a product with good nutritional characteristics and potentially applicable to the consumer market.